2018
DOI: 10.1017/aaq.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Cropping in an Age of Captive Taking: Exploring Evidence for Uncertainty and Food Insecurity in the Seventeenth-Century North Carolina Piedmont

Abstract: Engagement in sustained encounters with colonial actors had long-lasting demographic, social, and political consequences for Native American inhabitants of Southeastern North America during the colonial period (AD 1670–1783). Less clear is whether Native peoples who did not regularly trade with colonists also felt the destabilization experienced by more closely affiliated groups. This article explores Native lifeways in the seventeenth-century Eno River valley of the North Carolina Piedmont, a context for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A Proquest literature search conducted in December 2019 for the search terms "food insecurity AND disaster AND U.S." returned 1871 peer reviewed articles. A close review of the 100 most relevant articles in that search found that 54 articles were not focused on the United States (US), 36 articles focused on food or disasters but not both, four discussed food and disasters but were not food insecurity focused rather focused on aspects such as agricultural practices or disaster preparedness, one article was a historical piece on 17th century food insecurity [31], and one manuscript was a systematic literature review of the disaster literature [32]. The systematic review found that less than one percent of disaster research focuses on food [32], supporting our literature review finding of only three studies that directly address food insecurity outcomes following disasters in the US.…”
Section: Introductionmentioning
confidence: 99%
“…A Proquest literature search conducted in December 2019 for the search terms "food insecurity AND disaster AND U.S." returned 1871 peer reviewed articles. A close review of the 100 most relevant articles in that search found that 54 articles were not focused on the United States (US), 36 articles focused on food or disasters but not both, four discussed food and disasters but were not food insecurity focused rather focused on aspects such as agricultural practices or disaster preparedness, one article was a historical piece on 17th century food insecurity [31], and one manuscript was a systematic literature review of the disaster literature [32]. The systematic review found that less than one percent of disaster research focuses on food [32], supporting our literature review finding of only three studies that directly address food insecurity outcomes following disasters in the US.…”
Section: Introductionmentioning
confidence: 99%
“…The Jenrette site was occupied for only a short period of time-perhaps only 20 years-implying that the community was also aware of their tenuous position. This led them to prioritize short-term strategies over those that would have ensured longer term security and continuity (Melton, 2018(Melton, : 2167. Wider studies of Cherokee and Catawba communities have similarly yielded evidence for intensified foraging and increased consumption of seasonal, fleshy fruits, which not only grew on the boundaries of agricultural areas close to settlements but also required less processing (Fitts, 2015: 312-15;VanDerwarker et al, 2013).…”
Section: Living In a Broken World: Shatter Zones In Colonial North Americamentioning
confidence: 99%
“…In connection with the changes in settlement morphology discussed above, for example, the reduced lifespan of houses at the Townsend site noted by Marcoux (2010) reflects a tacit recognition of the uncertainty that permeated the lives of the nascent community residing there. Evidence for changing subsistence practices and foodways at the Jenrette and Ellery sites similarly reflects efforts of communities to mitigate for the impacts of resource scarcity, conflict, disease, and displacement by prioritizing short-term needs over longer term strategies (Hawkins et al, 2018;Melton, 2018). Disruption to trading networks may also be evidenced through the introduction of new cultural materials within burials and settlements, as well as a decrease in the visibility of materials that had previously been widely available (see, e.g.…”
Section: Towards An Archaeology Of the Shatter Zonementioning
confidence: 99%
“…Attacks could disrupt farming activities enough to cause food shortages and uncertainty (Jensen 2010; cf. van der Logt 2016:35), a problem faced by other Indigenous people in North America (Melton 2018). They also may have constrained other activities by women outside the village, such as ceramic raw material collection.…”
Section: Introductionmentioning
confidence: 99%